Analisis Resepsi Followers Gen Z Terhadap Kasus Pelecehan Seksual dalam Konten Kisah @Perempuanberkisah - Nababan, Ester Marini; Shabrina, Almira (Unitri Press, 2024)
Sexual harassment in Indonesia has continued to increase in various sectors ranging from education, public spaces and even families. Most of cases are found in public spaces and private relationships. A lot of victims feel silenced and do not dare to voice the cases experienced, resulting in psychological trauma. As technology developed, several communities began to emerge that used social media as a forum for victims' stories. One of them is an online community of women telling stories as a medium for women's empowerment and a story space for victims of sexual harassment. This story space is realized through story content that publishes the original stories of victims of sexual harassment. The authors used descriptive qualitative research methods and Stuart Hall's reception analysis theory to find out the meaning of Gen Z followers of the story content. Researchers collected data by interviewing 10 Gen Z @perempuanberkisah followers who come from different backgrounds. Object of this research is the perception of Gen Z followers obtained after going through the process of interpreting or decoding the content that has been presented. The result of this study is the meaning of Gen Z followers who tend to operate in the Negotiation position, namely accepting the story content message but still make a selection of the message. Abstrak Pelecehan seksual di Indonesia terus mengalami peningkatan dalam berbagai sektor mulai dari pendidikan, ruang public dan bahkan keluarga. Kebanyakan kasus ditemui pada ruang public dan hubungan private. Banyak korban yang merasa terbungkam dan tidak berani menyuarakan kasus yang dialami hingga mengakibatkan trauma psikis. Dengan perkembangan teknologi, maka mulai muncul beberapa komunitas yang menggunakan media sosial sebagai wadah cerita para korban. Salah satunya adalah komunitas online perempuan berkisah sebagai media pemberdayaan perempuan dan ruang cerita para korban pelecehan seksual. Ruang cerita tersebut direalisasikan melalui konten kisah yang mempublikasikan cerita asli para korban pelecehan seksual. Peneliti menggunakan metode penelitian deskriptif kualitatif dan teori analisis resepsi oleh Stuart Hall guna mengetahui pemaknaan Followers Gen Z terhadap konten kisah. Peneliti melakukan pengumpulan data dengan mewawancarai 10 orang Followers Gen Z @perempuanberkisah yang terdiri dari latar belakang berbeda-beda. Objek dari penelitian ini adalah persepsi followers Gen Z yang didapat setelah melalui proses pemaknaan atau decoding atas konten yang sudah disajikan. Hasil dari penelitian ini adalah pemaknaan followers Gen Z yang cenderung beroperasi pada posisi Negosiasi yaitu menerima pesan konten kisah namun masih melakukan seleksi terhadap pesan tersebut.